Analysis of Drug Distribution and Utilization Processes Using the Lean Hospital Method in the Outpatient Pharmacy Installation of Karanganyar Regency Hospital - Kresensia Stasiana Yunarti; Opstaria Saptarini; Ika Purwidyaningrum (International Journal of Public Health, 2025)
Improving service quality is a primary priority in hospital management. Service quality can be improved by reducing the percentage of non-value added activities through the Lean Hospital approach. This study aims to identify activities and analyze the root causes of critical waste in the drug distribution and utilization processes at the Outpatient Pharmacy Installation of Karanganyar Regency Hospital. This study is a non-experimental research with a qualitative descriptive design. Critical waste was obtained through the distribution of a waste weighting questionnaire assessed by all personnel involved in the drug distribution and utilization processes. The results show that the Value Stream Mapping calculation for the drug distribution process obtained a lead time of 147.41 minutes and a VAR value of 36%, while in the drug utilization process, compounded prescription service obtained a lead time of 128.53 minutes and a VAR of 24%, and non-compounded prescription service obtained a lead time of 75.8 minutes and a VAR of 26%. The critical waste questionnaire calculation using the Borda method in the drug distribution process showed overproduction 60%, inventory 53.33%, and waiting 43.33%, while in the drug utilization process, waiting 43.75%, overproduction 42.85%, and defect 39.70%. The 5S method, a Lean method, was used to eliminate waste in the service process at the Outpatient Pharmacy Installation of Karanganyar Regency Hospital.